Biocomparison Study of Adult and Paediatric Dose Strengths of the Prostacyclin Receptor Agonist Selexipag - Boehler, Margaux; Bruderer, Shirin; Ulč, Ivan; Dingemanse, Jasper (European journal of drug metabolism and pharmacokinetics, 2018)
BACKGROUND AND OBJECTIVES: Selexipag is an oral, non-prostanoid, selective prostacyclin receptor agonist recently marketed for the treatment of pulmonary arterial hypertension (PAH) in adults. Selexipag may also be an effective treatment in children with PAH. The aim of this study was to compare the pharmacokinetics of selexipag and its active metabolite ACT-333679 following single oral administration of one tablet of 200 µg selexipag (Treatment A) vs. 4 paediatric tablets of 50 µg (Treatment B) in healthy adult male subjects. METHODS: This was an open-label, randomized, two-treatment, two-period, crossover biocomparison study. Bioequivalence criteria were explored and safety variables (vital signs, electrocardiogram, and laboratory parameters) were assessed. RESULTS: The exploratory analysis showed that the 90% confidence intervals of geometric mean ratio (Treatment B/Treatment A) for maximum plasma concentration (C max), area under the plasma concentration-time curve from zero to infinity (AUC0-∞) of ACT-333679, as well as AUC0-∞ of selexipag, were within the bioequivalence interval (0.80, 1.25). In addition, no relevant difference in C max for selexipag between the two treatments can be concluded. Single oral dose administration of 200 µg selexipag as one tablet of 200 µg or four tablets of 50 µg was well tolerated. CONCLUSIONS: Pharmacokinetic characteristics of selexipag and its metabolite ACT-333679 following administration of one adult tablet of 200 µg selexipag and four paediatric tablets of 50 µg selexipag were comparable. TRIAL REGISTRATION: ClinicalTrials.gov identifier: NCT02745860.
Keywords: Acetamides; Pyrazines; klinické křížové studie; Humans; Healthy Volunteers; Therapeutic Equivalency; lidé středního věku; Dose-Response Relationship, Drug; mladý dospělý; dospělí; Administration, Oral; lidé; acetáty; Adult; acetamidy; Male; Middle Aged; Adolescent; pyraziny; Young Adult; vztah mezi dávkou a účinkem léčiva; terapeutická ekvivalence; Acetates; aplikace orální; zdraví dobrovolníci pro lékařské studie; Cross-Over Studies; mužské pohlaví; mladiství